2014
DOI: 10.1371/journal.pone.0089129
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Striatal BOLD Responses to Reward Anticipation and Reward Delivery in ADHD

Abstract: Altered reward processing has been proposed to contribute to the symptoms of attention deficit hyperactivity disorder (ADHD). The neurobiological mechanism underlying this alteration remains unclear. We hypothesize that the transfer of dopamine release from reward to reward-predicting cues, as normally observed in animal studies, may be deficient in ADHD. Functional magnetic resonance imaging (fMRI) was used to investigate striatal responses to reward-predicting cues and reward delivery in a classical conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 90 publications
6
60
0
Order By: Relevance
“…Although our finding differed from the frequently reported VS hyporesponsivity to reward anticipation in adults with ADHD (Plichta & Scheres, 2014), it is in line with recent studies demonstrating VS hyperresponsivity in individuals with ADHD during reward receipt (Furukawa et al, 2014;von Rhein et al, 2015). The divergent results may be explained by differences in the reward processing phase: anticipation, target, or receipt (Tripp & Wickens, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Although our finding differed from the frequently reported VS hyporesponsivity to reward anticipation in adults with ADHD (Plichta & Scheres, 2014), it is in line with recent studies demonstrating VS hyperresponsivity in individuals with ADHD during reward receipt (Furukawa et al, 2014;von Rhein et al, 2015). The divergent results may be explained by differences in the reward processing phase: anticipation, target, or receipt (Tripp & Wickens, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Showing a similar discontinuity, an fMRI study of neurotypical young adults showed activation in the right ventral and left dorsal striatum during reward anticipation in a classical conditioning paradigm, but no significant effects in the ADHD group. Conversely, upon receipt of rewards, never-medicated adults with ADHD demonstrated significantly greater responses in the ventral striatum bilaterally and in left dorsal striatum relative to controls [25]. Recently emerging resting-state functional MRI (fMRI) methods [26] have also been used to examine ventral striatal functional connectivity.…”
Section: Current Clues To the Neurobiology Of Adhdmentioning
confidence: 99%
“…ADHD symptoms and diagnosis, in contrast, have been predominantly characterized by lower VS responsiveness to reward-predicting cues (see 13 for meta-analysis and review, but see also 12 and subsequent commentary in 49 and 50). Neural activation to reward outcome has been less systematically studied in ADHD, with some evidence of relative hyper-responsiveness (12, 51, and 52, but see also 53 and 54). This discrepancy in relative VS activation to reward anticipation versus outcome may reflect impaired reward learning (51), consistent with evidence of impaired behavioral modification based on prior reinforcement history in ADHD (55).…”
Section: Discussionmentioning
confidence: 99%
“…Neural activation to reward outcome has been less systematically studied in ADHD, with some evidence of relative hyper-responsiveness (12, 51, and 52, but see also 53 and 54). This discrepancy in relative VS activation to reward anticipation versus outcome may reflect impaired reward learning (51), consistent with evidence of impaired behavioral modification based on prior reinforcement history in ADHD (55). Given the design of our functional paradigm, in which we compared mean VS activation across positive versus negative feedback blocks (with non-valence-specific cues), our results may more appropriately reflect emergent data linking ADHD to increased VS response to reward outcomes.…”
Section: Discussionmentioning
confidence: 99%